2016
DOI: 10.4102/jamba.v8i1.185
|View full text |Cite
|
Sign up to set email alerts
|

Modelling non-stationary annual maximum flood heights in the lower Limpopo River basin of Mozambique

Abstract: In this article we fit a time-dependent generalised extreme value (GEV) distribution to annual maximum flood heights at three sites: Chokwe, Sicacate and Combomune in the lower Limpopo River basin of Mozambique. A GEV distribution is fitted to six annual maximum time series models at each site, namely: annual daily maximum (AM1), annual 2-day maximum (AM2), annual 5-day maximum (AM5), annual 7-day maximum (AM7), annual 10-day maximum (AM10) and annual 30-day maximum (AM30). Non-stationary time-dependent GEV mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Furthermore, since the fundamental approach of this study is on the use of extreme value statistics using the block maxima, only the annual maximum value for each year was recorded and plotted in Figure 1. It is assumed that these AM1 data series are independent and identically distributed (iid) since they are blocked by years [9][10][11][12]. Similarly, it is also assumed that the annual maxima moving sums are also iid.…”
Section: Results and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, since the fundamental approach of this study is on the use of extreme value statistics using the block maxima, only the annual maximum value for each year was recorded and plotted in Figure 1. It is assumed that these AM1 data series are independent and identically distributed (iid) since they are blocked by years [9][10][11][12]. Similarly, it is also assumed that the annual maxima moving sums are also iid.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…The approach used in this study is block maxima. In hydrological studies, when sample sizes are large it is natural to block observations by years [9,10].…”
Section: Study Sites Data and Block Maxima Moving Sumsmentioning
confidence: 99%
“…. , X n constitute five day maximum losses that are distributed with the GEVD in model ( 5), Maposa et al (2016) showed that in period t, r t follows GEVD(µ(t), ξ, σ) and Bee (2012) emphasised that µ(t) = µ 0 + µ t 1 for a linear variation in location with an intercept parameter µ 0 and a slope parameter µ 1 , that expresses the rate of change in daily losses. We finally express our proposed hybrid for extreme return losses as r t ∼ SARI MA(p, d, q) × (P, D, Q) − MS(k) − EGARCH(p, q) − GEVD(xi, µ t , σ t ).…”
Section: Methodsmentioning
confidence: 99%
“…According to Maposa et al (2016), a 100(1 − α)% Bayesian credible set C (or, in particular, credible interval) is a subset of the space parameter Θ, such that…”
Section: Bayesian Markov-chain-monte-carlo Frameworkmentioning
confidence: 99%
“…A substantial part of the variability in the data can probably be explained by a systematic variation in rainfall over the years. One way of capturing this trend is by allowing the GEVD location and scale parameters to vary with time [40]. From Figure 2 a simple linear trend in time seems plausible for our annual maximum rainfall X t , and we can use the model…”
Section: Non-stationary Gevd Modelling Of Annual Block Maxima Rainfall Datamentioning
confidence: 99%